1996
DOI: 10.1046/j.1464-410x.1996.82321.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐surgical recurrent varicocele: efficacy of internal spermatic venography and steel‐coil embolization

Abstract: Internal spermatic venography allowed a precise anatomical definition of the recurrent varicocele and the use of steel-coil embolization provided satisfactory improvements in sperm quality and paternity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 3 publications
0
36
0
1
Order By: Relevance
“…Varicocelectomy is the most frequently performed operation for the management of male infertility [7, 8, 10]. The principle of the surgical treatment is to obstruct the dilated veins that drain into the pampiniform plexus [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varicocelectomy is the most frequently performed operation for the management of male infertility [7, 8, 10]. The principle of the surgical treatment is to obstruct the dilated veins that drain into the pampiniform plexus [9].…”
Section: Introductionmentioning
confidence: 99%
“…With the evolution and progress of interventional radiology, less invasive methodology has entered the field presenting alternative choices of treatment to open surgery. Percutaneous embolization with coils has been used by many investigators [8, 12, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Some authors prefer retrograde venography and sclerotherapy for treatment of postsurgical recurrent varicocele. Clinical studies, however, demonstrate only limited success rates of retrograde embolization of 78–85% [18, 19]in these cases. Our results demonstrate that microsurgical varicocele ligation can be combined effectively with antegrade sclerotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques have a recurrence rate that ranges from 5 to 45% [6, 7]. These recurrences are usually the result of residual venous communications from mid retroperitoneal or low inguinal parallel collaterals [8, 9]. Radiologic embolization techniques are also associated with high recurrence rates ranging from 2 to 64% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although physical examination is most commonly used to detect the presence of a clinical varicocele [1, 13], methods using radiologically documented recurrence after varicocele repair are still controversial [14]. Some authors have reported that selective internal spermatic venography (SISV) is helpful to document varicocele recurrence [8, 9, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%